The Power of Ice Breaker Activity: Examining the Impact of Icebreakers on Student Participation and Engagement in the Classroom - Richie Ynot Mepieza (Journal of Learning on History and Social Sciences, 2024)
This study explores the importance of creating a comfortable and respectful classroom environment through the use of icebreaker activities. The study analyzes the opinions of six students on ways to improve or modify icebreaker activities to promote engagement and participation in the classroom. The results of the study reveal that icebreaker activities are essential in building a positive and productive learning environment. The students believe that icebreakers help to improve their speaking and listening skills, as well as their mood and brain activation. They also feel that icebreakers create a safe learning space and promote flexibility and willingness to learn. Furthermore, the students stress the importance of wise selection and modification of icebreaker activities to ensure that they have a positive impact on students and promote engagement in the classroom. The students suggest that icebreakers should be used at the beginning of each class to help energize and motivate students. Additionally, the students believe that clear expectations for student behavior are critical in creating a safe and respectful classroom environment. They stress the need to minimize threats or distractions that could interrupt the flow of learning. This study highlights the importance of creating a comfortable and respectful classroom environment through the use of icebreaker activities. The findings suggest that icebreakers can be modified to better promote engagement and participation in the classroom, ultimately leading to a positive and productive learning environment for students.